2018
DOI: 10.1021/acs.biochem.8b00973
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Responsive Protein Design: Design of a Small Protein Motif Dependent on Glutathionylation

Abstract: Cysteine S-glutathionylation is a protein post-translational modification that promotes cellular responses to changes in oxidative conditions. The design of protein motifs that directly depend on defined changes to protein side chains provides new methods to probe diverse protein post-translational modifications. A canonical, 12-residue EF Hand motif was redesigned to be responsive to cysteine glutathionylation. The key design principle was the replacement of the metal-binding Glu12 carboxylate of an EF Hand w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…The conserved, bidentate interaction with metal by Glu12 renders that position particularly favorable as a site of modification for PTM-responsive protein design. We have previously demonstrated that phosphoserine, phosphothreonine, phosphotyrosine, or glutathionylated cysteine can mimic Glu12, bind terbium, and exhibit robust terbium luminescence, including in the presence of physiological concentrations of Ca 2+ and Mg 2+ . In contrast, unmodified Ser, Thr, Tyr, or Cys poorly mimics Glu and exhibits substantially weaker terbium binding and terbium luminescence.…”
Section: Resultsmentioning
confidence: 99%
“…The conserved, bidentate interaction with metal by Glu12 renders that position particularly favorable as a site of modification for PTM-responsive protein design. We have previously demonstrated that phosphoserine, phosphothreonine, phosphotyrosine, or glutathionylated cysteine can mimic Glu12, bind terbium, and exhibit robust terbium luminescence, including in the presence of physiological concentrations of Ca 2+ and Mg 2+ . In contrast, unmodified Ser, Thr, Tyr, or Cys poorly mimics Glu and exhibits substantially weaker terbium binding and terbium luminescence.…”
Section: Resultsmentioning
confidence: 99%
“…[35][36][37][38][39] We recently described the development of a short motif (DKDADGWC) responsive to cysteine glutathionylation, with increased Tb 3+ binding and Tb 3+ luminescence in the glutathionylated peptide relative to the unmodified (free cysteine) peptide (Figure 3). 50 In that design, the additional metal-binding functionality was provided by one or both carboxylates of the glutathione conjugated to cysteine. We have also previously described similar EF-Hand-based phosphorylation-responsive sequences dependent on serine phosphorylation at residue 12, or tyrosine phosphorylation at residue 11 or 15.…”
Section: Discussionmentioning
confidence: 99%
“…This approach was subsequently applied, using appropriate consideration of differences in protein geometry of the resultant metal-binding residues, to the design of protein motifs responsive to tyrosine phosphorylation and to cysteine glutathionylation. 50 We sought to develop a minimally sized protein motif responsive to phosphorylation. The development of alternative approaches was also expected to increase the range of protein kinases for which sensors could be designed.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that they may be used for nitro-tyrosine formation, but there is no evidence of the conserved region used by Urmey and Zondlo [ 41 ]. In a similar way, looking for the cysteine residues which may be glutathionylated [ 43 ], there is no evidence of this sequence being in the hydrogenase amino acid sequences investigated here ( Figure 1 ). From what can be considered a rather naïve point of view, using bioinformatics, it is therefore possible that hydrogenases in higher organisms are inhibited by NO through thiol modification, and possibly by ROS, but as yet there is little evidence that such control is significant.…”
Section: Hydrogenases Of Higher Plantsmentioning
confidence: 91%
“…Others have designed a motif which may be glutathionylated [ 43 ]. This sequence is similar to the nitration sequence, both being based on EF-hand motifs.…”
Section: Hydrogen Production By Chlamydomonas Reinhardtimentioning
confidence: 99%